Algebraic thinking skills of madrasah tsanawiyah (MTs) students in solving algebraic problems - Daroini, Mustain Bagus; Subanji, Subanji; Irawati, Santi (AXIOM : Jurnal Pendidikan dan Matematika, 2025)
Algebra is a fundamental topic in the mathematics curriculum at Madrasah Tsanawiyah (MTs), yet many students continue to face challenges in solving algebraic problems. This study aims to examine the algebraic thinking skills of eighth-grade students at MTs Unggulan PP Amanatul Ummah Surabaya, particularly through number-oriented and structure-oriented approaches. A descriptive qualitative method was employed, involving 61 students as participants. The instruments included an algebraic thinking test incorporating visual illustrations and in-depth interviews with six selected students representing high, medium, and low ability levels. The findings reveal that only high-ability students were able to effectively apply structure-oriented algebraic thinking. The majority of students demonstrated moderate-level skills, with primary difficulties in constructing mathematical models based on problem structures. These results underscore the importance of instructional strategies that cultivate students’ structural reasoning in algebra. The study provides valuable insights for educators to design learning activities that support the development of students' algebraic thinking, and it serves as a reference for future research to explore targeted interventions aimed at enhancing algebraic problem-solving abilities in MTs students.